Urolithin A Attenuates Hyperuricemic Nephropathy in Fructose-Fed Mice by Impairing STING-NLRP3 Axis-Mediated Inflammatory Response via Restoration of Parkin-Dependent Mitophagy - Zhang, Cong; Song, Yingying; Chen, Liang; Chen, Peng; Yuan, Ming; Meng, Yan; Wang, Qi; Zheng, Guohua; Qiu, Zhenpeng (Frontiers in Pharmacology, 2022)
Urolithin A (UroA) is one of the primary intestinal metabolites of ellagitannins, showing translational potential as a nutritional intervention in humans. Mounting evidence suggests that fructose consumption contributes to the progression of chronic kidney disease (CKD) that manifests in hyperuricemic nephropathy, renal inflammation, and tubulointerstitial injury. Here, we investigated the efficacy of UroA in alleviating fructose-induced hyperuricemic nephropathy in mice. Uric acid-exposed human kidney-2 (HK-2) cells were utilized for in vitro mechanism validation. Histopathological staining, immunoblotting, and transmission electron microscope were performed for the mechanistic investigations. Our results revealed that UroA ameliorated fructose-induced hyperuricemic nephropathy in mice. The histopathologic assessment showed that UroA attenuated tubular hypertrophy and dilation, glomerular basement membrane thickening, and collagen deposition in the kidney of fructose-fed mice. Mechanistically, UroA treatment impaired STING-NLRP3 activation, resulting in reduced production of proinflammatory cytokines IL-1β, IL-6, and TNF-α. Notably, UroA exhibited a scavenging effect against reactive oxygen species (ROS) and restored fructose-impaired PINK1/Parkin-mediated mitophagy in nephropathic mice. Furthermore, the inhibitory effect of UroA in STING-NLRP3 activation was impaired after Parkin gene silencing in HK-2 cells. Together, this study suggests that UroA alleviates fructose-induced hyperuricemic nephropathy by promoting Parkin-dependent mitophagy, thereby suppressing STING-NLRP3 axis-mediated inflammatory response. Thus, dietary supplementation with UroA or ellagitannins-rich foods may serve as a promising intervention to prevent CKD progression.